2011
DOI: 10.1111/j.1467-8624.2010.01533.x
|View full text |Cite
|
Sign up to set email alerts
|

Teacher-Child Relationships and the Development of Academic and Behavioral Skills During Elementary School: A Within- and Between-Child Analysis

Abstract: Despite recent growth in research highlighting the potential of teacher-child relationships to promote children's development during the early years of school, questions remain about the importance of these relationships across elementary school. Using data from the NICHD Study of Early Child Care (N = 1,364), this study examines between- and within-child associations between teacher-child relationship quality and children's academic achievement and behavior problems from kindergarten (ages 4-6 years) through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
90
2
7

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 141 publications
(105 citation statements)
references
References 47 publications
6
90
2
7
Order By: Relevance
“…When positive, these relationships are associated with improvement in school performance and reduction in behavior problems (Maldonado-Carreño & Votruba-Drzal, 2011), as well as the development of social skills (Berry & O'Connor, 2010). Moreover, as the students progress in elementary school, the importance of these relationships for the development remains constant (Berry & O'Connor, 2010;Maldonado-Carreño & Votruba-Drzal, 2011).…”
Section: The Role Of School In the Development Of Childrenmentioning
confidence: 99%
See 2 more Smart Citations
“…When positive, these relationships are associated with improvement in school performance and reduction in behavior problems (Maldonado-Carreño & Votruba-Drzal, 2011), as well as the development of social skills (Berry & O'Connor, 2010). Moreover, as the students progress in elementary school, the importance of these relationships for the development remains constant (Berry & O'Connor, 2010;Maldonado-Carreño & Votruba-Drzal, 2011).…”
Section: The Role Of School In the Development Of Childrenmentioning
confidence: 99%
“…Studies on the teacher-student relationship with children in U.S. elementary schools have demonstrated their relevance to the socioemotional development in childhood (Berry & O'Connor, 2010;Maldonado-Carreño & Votruba-Drzal, 2011;O'Connor & McCartney, 2006). When positive, these relationships are associated with improvement in school performance and reduction in behavior problems (Maldonado-Carreño & Votruba-Drzal, 2011), as well as the development of social skills (Berry & O'Connor, 2010).…”
Section: The Role Of School In the Development Of Childrenmentioning
confidence: 99%
See 1 more Smart Citation
“…Dessa forma, alunos que apresentam relacionamentos de alta qualidade com seus docentes têm melhor desempenho escolar (Berry & O´Connor, 2010;Maldonado-Carreño & Votruba-Drzal, 2011;Pianta & Stuhlman, 2004).…”
Section: Introductionunclassified
“…nlthough relationships with parents are most significant in shaping children's development, a growing body of literature suggests that relationships between children and teachers shape children's development in various aspects during the early school years (Maldonado-Carreño & Votruba-Drzal, 2011). A number of researchers have demonstrated that the quality of the teacher-child relationship affects the well-being of the child across a wide range of domains, including peer socialisation, emotional and behaviour problems, classroom adjustment and intellectual abilities (Mitchell et al, 2008;Smith et al, 2000;Sylva et al, 2003).…”
Section: Teachers' Pedagogical Skillsmentioning
confidence: 99%